1985 - Millar, Mark 1969-; Workman, John (Marvel Publishing Inc, 2008)
A young outcast immerses himself in comic books, preferring them to his real life in dreary 1985. But when the absolute worst members of the world's fictional universe invade the real world, he has trouble making people believe him - until the bodies start piling up